Remediasi Miskonsepsi Hukum Newton melalui HOTS (Higher Order Thinking Skills) - Anis Pamilih; Marmi Sudarmi; Alvama Pattiserlihun (Radiasi : Jurnal Berkala Pendidikan Fisika, 2019)
This research tries to give an example for teaching HOTS in accordance with the goverment’s demands on the 2013 curriculum in remediating misconceptions “canoot distinguish between Newton’s First Law and Newton’s Third Laws”. The purpose of this research is to know students’ understanding after learning about misconception remediation. This research used classroom action research methods which will be analyzed qualitatively. Assessment instruments used lesson plans, observation sheets, questionnaire sheets, and evaluation tests. Based on the observation sheet as many as 83,65% students can answer correctly the herding questions submitted by the teacher. This is supported based on the questionnaire sheet as much as 95,18% of students stated that they could understand the herding questions and felt helped by the accompanying questions to distinguish Newton’s First Law and Newton’s Third Laws. From the results of the evaluation test questions, 83,33% of students received grades ≥70. The results of observation sheets, questionnaires, and evaluation questions have met the criteria of success, it can be concluded that herding questions made so that students can learn to think HOTS can be used to remedy “cannot distinguish between Newton’s First Law and Newton’s Third Laws”.